Eight weeks of treatment with probiotic Bifidobacterium breve, Bif195 lowers fatigue scores in patients with diarrhoea-predominant irritable bowel syndrome: results from a randomised, clinical trial - Grønbæk, Ida Marie Bruun; Halkjær, Sofie Ingdam; Hansen, Esben Holm; Mollerup, Sarah; Paulsen, Sarah Juel; Konrad, Christina Valbirk; Engel, Sara; Bulinska-Balas, Magdalena; Wellejus, Anja; Haaber, Anne Birgitte; Christensen, Alice Højer; Engsbro, Anne Line; et al. (Frontiers in Nutrition, 2026)
Patients with irritable bowel syndrome experience abdominal pain and stool habit disturbances, and often also extraintestinal symptoms, such as fatigue. The disorder is linked to gut dysbiosis, and manipulation of the microbiota is considered a possible treatment strategy. This randomised, double-blinded, placebo-controlled study aimed to investigate the effects of the probiotic strain Bifidobacterium breve, Bif195™ (DSM 33360) (Bif195), on symptoms and gut microbiome composition in patients with diarrhoea-predominant irritable bowel syndrome. Sixty-one patients with moderate–severe disease activity were allocated to 8 weeks of treatment with either Bif195 or placebo (1:1), followed by 8 weeks of follow-up. The primary outcome was a change in symptom scores measured by the validated questionnaire, IBS-symptom severity scale. Secondary and explorative outcomes were the effects of Bif195 on intestinal symptoms, quality of life, fatigue, and the gut microbiota. Modulation of the transepithelial electrical resistance (TEER) of Caco-2 cells by Bif195 was investigated in vitro as a model of barrier integrity. The results showed no effect of Bif195 on primary or secondary outcomes; however, Bif195 lowered fatigue scores compared to placebo. Significantly increased TEER readings in vitro indicated enhanced barrier integrity, suggesting GI permeability as a mechanism for further clinical exploration.Clinical trial registrationclinicaltrials.gov, identifier NCT04808271.